(untitled) (Psychology Travelogs, 2021)
This article is devoted to the analysis of possibilities of integration of methods of psychodiagnostics of authenticity of the person. The concept of personality authenticity in the context of an integrative approach to psychological science and practice is considered. It has been found that in scientific research, authenticity is most often associated with existential and humanistic psychology, the prevailing understanding of authenticity is contained in Gestalt therapy, where it is defined as a person’s conformity to himself, the ability to live without betraying his true self. Methods of research of authenticity are analyzed, ways of their integration in complex empirical researches and practical researches are defined. This article offers the arrangement, psychological interpretations of the results of the empirical part of the research of the teacher’s authenticity peculiarities. Authenticity is an important quality of the teachers who, along with identity, forms the basis of their professional competence. However, in Ukraine there are no adapted diagnostic methods for personality authenticity study. In such circumstances, adaptation to the Ukrainian sample of Authenticity Scale (Wood & Linley, 2007) and Authenticity Inventory (Kernis & Goldman, 2005) is very relevant. According to the results of the reliability check of Authenticity Scale in the Ukrainian translation, this methodology is a reliable tool for authenticity research (α = 0.93). All indicators of alpha Kronbach’s AI-3 questionnaire in the Ukrainian-language translation are in the range of 0.84 and 0.93, which indicates the high reliability of the subscale of this questionnaire. Results of Correlation Analysis of Authenticity Questionnaires and AI-3 showed the existence of significant positive relationships between these methods (r: min = 0.500, max = 0.961), which proves their possibility of application in the complex study of the identity of the individual. We have found that teachers are characterized by an average level of authenticity, which testifies to the understanding of the teachers of their true self, but the impossibility of its best to show, due to certain requirements for professional teaching activities, the need to answer more social role than to show their individuality. Teachers are characterized by such a component of authenticity as "orientation on relationships", that is, openness and honesty in interaction with other people.